The Crisis of Arab Thought between Heritage and Reality Transformation in Contemporary Arab ThoughtMohammad - Al-Shiyyab, Mohammad (Jordan Journal of Social Sciences, 2019)
This paper seeks to demonstrate how contemporary Arab thought addressed heritage. It is evident that heritage is not part of contemporary Arab thought since it is considered as a historical difference between the status quo and the historic past. Therefore, when examining it, it was detached from its circumstances and considered as metaphysics to assure its continuity and comprehensive validity. Metaphysics here indicates abandoning the historic effect as a factor in creating a difference between the Arab Islamic cultures in the past (Heritage) and the status quo of culture (the present). The interest in heritage, accordingly, is an ill phenomenon which tries to resurrect the dead past. We started considering it as a fully- fledged independent entity that opposes the Arab present. This indicates that we see them as two different entities: The Arab heritage and the Arab present. Nonetheless, the real beginning of the contemporary Arab thought cannot be established unless on an objective historic analysis of heritage and a historic analysis of the changing cultural conditions that are capable of addressing questions on the Arab present.